Advances in heat transfer. Volume 40, - Fridman, A.; Cho, Young I. (Advances in heat transfer, 2007)
Advances in Heat Transfer fills the information gap between regularly scheduled journals and university level textbooks by providing in-depth review articles over a broader scope than in journals or texts. The articles, which serve as a broad review for experts in the field, will also be of great interest to non-specialists who need to keep up-to-date with the results of the latest research. It is essential reading for all mechanical, chemical and industrial engineers working in the field of heat transfer, graduate schools or industry. * Provides an overvi.